Desarrollo de un sistema de ventilación forzada para el sector de Latacunga - Guamúshig Alpusig, Darwin Javier (2022)
The present project developed as a technological proposal focuses on the evelopment of a forced ventilation system for the Latacunga sector, in a simulation laboratory, lectrical and electromechanical test located in the San Felipe neighborhood. The ventilation system has a logic programmer model LOGO 12/24 RCE V8.2, whose programming was developed in the LOGO!Soft Comfort V8.2 software, executing output signals for the automation of the system, as well as a presence sensor and a temperature. For the dimensioning of the ventilation system, it is carried out through calculations of the necessary air flow applying the ASHRAE heating Ventilating and AIR-CON DITIONINIG APPLICATIONS regulations, the main purpose is to improve thermal comfort within the laboratory. The technological proposal was carried out through an experimental type design where technical guides, regulations associated with the development of the system, testing of the location of fans in different places and positions are used to guarantee the correct functioning, tests were carried out, temperature measurements with the EXTECH HT30 thermal stress and a control system operation manual.